BASIC FEATURES OF EDUCATIONAL QUALITY MANAGEMENT IN HIGHER EDUCATIONAL INSTITUTIONS (SOCIOLOGICAL ANALYSIS) (Archive of Conferences, 2020)
This article examines the problems of improving the quality of education and provides a sociological analysis of the main features of the formation of the quality management system of education. topical issues such as the creation of new methods and algorithm developments for determining the quality of components were analyzed.